TIPE FOKALISASI DALAM NOVEL TRILOGI SOEKRAM KARYA SAPARDI DJOKO DAMONO (KAJIAN TEORI NARATOLOVI MIEKE BAL) - Muh As'ad; Nengsilianti Nengsilianti; Suarni Syam Saguni (Kantor Bahasa Provinsi Maluku Utara, 2021)
The study aims to describe focalization by using Mieke Bal's naratology study. This research is a qualitative and uses narratological interpretation. The data collection technique is a documentation technique, namely reading and noting the data by the research focus. The collected data is taken from novel Soekram Trilogy by Saaprdi Djoko Damono that is identified, classified, and analysed. The results showed that novel Soekram Trilogy was more dominant in using narrators from outside the fabula (story) compared to narrators from figures inside the fabula. This happened because there are many external focalizers related the events that occur in the novel so that the narrator is more active in every event flows in the story.